Thrombocytopenia following kidney transplantation: a frequent, underestimated and potentially severe complication - Léonard, Cédric; Taton, Benjamin; Lazaro, Estibaliz; Merville, Pierre; Viallard, Jean-François; Couzi, Lionel; Rivière, Etienne (Frontiers in Immunology, 2025)
IntroductionCytopenias occur frequently after kidney transplantation but posttransplantation thrombocytopenia (PTTCP) frequency has rarely been reported.MethodsThis monocenter, retrospective study aimed to describe PTTCP frequency, causes, treatments and outcomes. PTTCP was defined as thrombocytopenia with ≥2 platelet counts <100×109/L after first month posttransplantation.ResultsAmong 2118 kidney-transplant recipients between 2002 and 2018, 189 (8.9%) developed PTTCP. Their mean platelet-count nadir was 51×109/L [range 4-96×109]; nadir was <50×109/L for 87 (46.0%) patients. Main identified PTTCP etiologies were drugs (24.3%), or infectious diseases (20.1%; cytomegalovirus causing 79.4% of them), or unknown for 26 (13.7%). Bleeding rate was high (32.7%), with 40 (64.5%) severe episodes. During follow-up, 103 (54.5%) patients suffered graft loss or died at a median of 5.41 years post-PTTCP episode. Multivariate analyses retained a severe bleeding episode as being significantly associated with antiplatelet or anticoagulation therapy and pancytopenia, and age, creatininemia, transplantation-to-PTTCP interval and severe bleeding as significant risk factors for death or graft loss.ConclusionPTTCP is frequently associated with severe bleeding, which is a risk factor for graft loss and death. Those findings suggest that the risk/benefit ratio of antiplatelet or anticoagulation therapies should be systemically evaluated for PTTCP patients.